Gendered Language: A Critical Discourse Analysis of Pakistani Dramas - Kiani, Sadaf; Umar, Lubna; Sultan, Ameer (Pakistan Journal of Humanities and Social Sciences, 2023)
This study analyzes language used by female characters in selected Pakistani Dramas to explore how discourse plays a role in gender construction and its impact in revealing the ideology of the speakers in the Pakistani context. This study employs van Dijk’s critical discourse analysis approach and Robin Lakoff’s deficit approach towards gendered language as its research framework. It investigates that gender biased discourse portrays females as dependent, indecisive, weak and lacking in confidence. The study investigates gender disparities in depiction of male and female characters in these dramas and explores the role of media discourse in constructing stereotypical image of women in Pakistani Urdu dramas. It also highlights the changing trends in the Pakistani context. The study highlights a total of five linguistic features which includes tag questions, lexical hedges, adjectives, polite expressions and use of questions to represent the image of females in Pakistani Urdu dramas. The analysis reveals that gendered stereotypes are being broken using linguistic features by the female characters. Language used for conforming is now being reverted and used to confront instead. Moreover, the use of empty adjectives, it was seen are used by both genders equally.